EFFECT OF TOPPING AND PLANT DENSITIES ON GROWTH AND YIELD OF COTTON. - & Al-Naqeeb, Hasab (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this study was to investigate the effect of topping and plant densities on growth and yield of cotton (Gossypium hirsutum L.) .A field experiment was conducted at the research station of Field Crop Department-  College of Agricultural Engineering Sciences - University of Baghdad,during  two summer seasons (2016 and 2017).This study included two factors using Ranndomiled Complele Block Design within split plot arrangement  .The first factor, regulate growth  through foliar with the growth retardants (pix) at the beginning of flower buds appearance , foliar at the beginning of The flower appearance and growing tips topping at the  beginning of flower buds appearance and  tip topping at the beginning of flower appearance and control  (without topping). These treatments occupied the main  plots .The second factor was the number of plants in hill (1,2 and 3 plant hill-1),which occupied the  sub plots. The results indicated significant differences among regulate growth traetment in most studied characters, P2 was exceeded by producing the highest number of branches and number of open bolls .This causes to increase plant yield , which  reach 23.78  and 22.86 g plant-1 and  seed cotton yield giving2124.8 and 1972.3 kg ha-1, whereas treatment T4 had the highest average in dry weight, lint length and lint fineness. The treatment 1 plant   hill-1 was exceeded by producing  the highest   plant height,  number of sympodia, leaf area, dry weight, boll weight and the number of open  bolls which reflected on increasing plant yield by (32.63 and 34.58) g plant-1 and lint fineness by (4.66 and 4.72) micronear for both seasons respectively . The results indicated a significant interaction between regulate growth  treatments and number of plants per hill in some studied characters. This indicate that the responce of cotton topping differed due to plant densities,with topping.